Pharmacokinetic Evaluation of a Drug Transporter Cocktail Consisting of Digoxin, Furosemide, Metformin, and Rosuvastatin. Issue 3 (29th July 2016) - Stopfer, P; Giessmann, T; Hohl, K; Sharma, A; Ishiguro, N; Taub, ME; Zimdahl‐Gelling, H; Gansser, D; Wein, M; Ebner, T; Müller, F
Abstract : This article reports the clinical investigation of a probe drug cocktail containing substrates of key drug transporters. Single oral doses of 0.25 mg digoxin (P‐gp), 5 mg furosemide (OAT1 and OAT3), 500 mg metformin (OCT2, MATE1, and MATE2‐K), and 10 mg rosuvastatin (OATP1B1, OATP1B3, and BCRP) were administered separately or as a cocktail in a randomized six‐period crossover trial in 24 healthy male volunteers. As a cocktail, relative bioavailabilities of digoxin and metformin and furosemide AUC0‐tz were similar to separate dosing. However, when administered as a cocktail the Cmax of furosemide was 19.1% lower and the Cmax and AUC0‐tz of rosuvastatin were 38.6% and 43.4% higher, respectively. In addition, the effects of increased doses of metformin or furosemide on the cocktail were investigated in 11 and 12 subjects, respectively. The cocktail explored in this trial has the potential to be used for the in vivo screening of transporter‐mediated drug–drug interactions. © 2016 American Society for Clinical Pharmacology and Therapeutics